2016
DOI: 10.1039/c5py01444a
|View full text |Cite
|
Sign up to set email alerts
|

Azide-based heterobifunctional poly(ethylene oxide)s: NaN3-initiated “living” polymerization of ethylene oxide and chain end functionalizations

Abstract: Sodium azide (NaN3)-initiated “living” ring-opening polymerization of ethylene oxide and chain end functionalizations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…Regiochemistry of α-Azido-ω-hydroxy Poly(glycidyl phenyl ether). The regioregularity of PGPE samples synthesized with both initiating systems, N 3 NBu 4 and N 3 NBu 4 /iBu 3 Al, was investigated by 13 C NMR (Figure S5). Assignment of triad regiosequences was done according to our previous study.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regiochemistry of α-Azido-ω-hydroxy Poly(glycidyl phenyl ether). The regioregularity of PGPE samples synthesized with both initiating systems, N 3 NBu 4 and N 3 NBu 4 /iBu 3 Al, was investigated by 13 C NMR (Figure S5). Assignment of triad regiosequences was done according to our previous study.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…They successfully polymerized a variety of monomers including ethylene oxide, propylene oxide, ethoxyethyl glycidyl ether, and epichlorohydrin. Kim et al 13 recently demonstrated that initiation of ethylene oxide with NaN 3 can be used to generate azide-terminated poly(ethylene oxide) through an AROP mechanism. Kakuchi et al 14 also reported a convenient way to synthesize azido-terminated polyethers by using hydroxyazides as initiator and a phosphazene base as a catalyst.…”
Section: ■ Introductionmentioning
confidence: 99%
“…α-Functionalization: strong bases like hydroxides, alkoxides, metal–alkyls, azides and -aryls are employed for oxyanionic polymerization (vide supra) . These initiators may contain an orthogonal, sometimes latent functionality that can be introduced via the initiation step (see Table ).…”
Section: Poly(alkylene Oxide) Structures: Innovative Polyether Struct...mentioning
confidence: 99%
“…Further, if protecting groups are used, they should be easily removable to release the functionality subsequent to the polymerization. 39,73,239−242 α-Functionalization: strong bases like hydroxides, alkoxides, metal−alkyls, azides 243 and -aryls are employed for oxyanionic polymerization (vide supra). 244 These initiators may contain an orthogonal, sometimes latent functionality that can be introduced via the initiation step (see Table 1).…”
Section: Multifunctional Pegsmentioning
confidence: 99%
“…This method limits the availability of functional groups, as they have to tolerate the strongly basic conditions of the oxyanionic polymerization. Furthermore, the synthesis needs to be carried out under inert atmosphere to exclude polymer chain growth initiated by traces of water and requires handling of the toxic gas EO. (ii) The second method involves iterative coupling reactions of heterobifunctional oligomers to build up OEGs and PEGs. This method requires considerable synthetic effort and purification in between the individual coupling steps. , (iii) Another strategy consists of a monofunctionalization of readily available OEG/PEG-diol with a functional group and subsequent (chromatographic) isolation of the desired heterobifunctional PEG molecule.…”
Section: Introductionmentioning
confidence: 99%